Modeling urban growth boundary based on the evaluation of the extension potential: A case study of Wuhan city in China. (February 2018) - He, Qingsong; Tan, Ronghui; Gao, Yuan; Zhang, Mengke; Xie, Peng; Liu, Yaolin
Abstract: The urban growth boundary (UGB) concept is useful in the field of urban planning, but models that can simulate the change in UGBs remain limited to date. In this paper, we propose a model known as UBEM that can simulate the future UGB. UBEM combines historical trajectories of UGB development and its extension potential in each azimuth to predict the future UGB for one city. UBEM consists of two parts: 1) the radiation method (RM) is used to describe the incremental length between the urban boundaries. In RM, urban centroids are used as the origin points to generate a set of radial lines from each azimuth, and we calculate the total and annual urban boundary length increments for each azimuth. 2) the extension pressure of the urban boundary is evaluated for different azimuths based on the potential value, which is generated by selecting a set of variables that are related to urban growth potential. Multiple time series maps were used to calibrate the model to reduce the randomness in future modeling. We compare the calibrated modeling result with those generated by the uncalibrated UBEM and a separate null model, applying two goodness of fit metrics to evaluate model accuracy: percent area match (PAM) quantity and PAM location were used to demonstrate that the calibrated UBEM performed better than the uncalibrated UBEM and null model when modeling the change in the urban boundary. Wuhan City in central China is used as a case study to test the viability of UBEM and predict the future UGB in 2020. The predication result offers helpful guidelines for Wuhan's future urban planning and UGB design. Highlights: A UBEM model was designed to simulate the urban growth boundary. Multi-temporal data were used to calibrate the model coefficients. UBEM out-performs the null model in modeling the urban growth boundary. Wuhan was used as a case study to test the viability of UBEM.